Preliminary 40Ar-39Ar analyses of igneous and metamorphic rocks from the Napier Complex - Takigami, Yutaka; Ishikawa, Naoto; Funaki, Minoru (National Institute of Polar Research, 1998)
P(論文) Ages of two gneisses and two dolente dykes which were collected for a paleomagnetic study from Mt Riiser-Larsen in the Napier Complex, East Antarctica, were analyzed by the ^<40>Ar-^<39>Ar method All samples contain excess Ar Based on their age spectra, however, ages of about 800-1100 Ma which are similar to those of Amundsen dykes have been estimated for the dolerite samples One gneiss indicates an age of about 2000 Ma as the upper limit This age might correspond to a thermal event which has not been reported departmental bulletin paper